Spatial Perception and Cognition Review. Considering Geotechnologies as Urban Planning Strategy - Júnia Borges; Camila Zyngier; Karen Lourenço; Jonatha Santos (TeMA: Journal of Land Use, Mobility and Environment, 2014)
This article proposes a review of the spatial cognition and perception principles, referring to the definition proposed by Cullen and Lynch, through the geotechnology tools. It presents a case study to be analyzed through Geographical Information Systems (GIS), 3D Modeling, Spatial Analysis and Data Base Structure. This proposition presents reflections about the concepts and values of the early foundations of the spatial perception and cognition theories as a base to promote participative planning, investigating how geotechnologies can favor the registration and identification of landscape values to be considered in urban planning. The downtown of Belo Horizonte (Brazil) was defined as a case study to promote the exercise of these reflections, aiming to present a practical illustration of the methodological proposition. This work tried to reach its purpose inquiring how geotechnologies could enhance knowledge gain in the Urban Planning practice. It points out some research paths that could be followed, as well as new approaches to the development of academic understanding of the geotechnologies role in the urban planning scenario.